Komposisi Dan Karateristik Jaringan Karkas Domba Ekor Tipis Yang Diberi Ransum Berbasis Indigofera zollingeriana Pada Sistem Pemeliharaan Yang Berbeda - Jatnika, A. R.; Yamin, M.; Priyanto, R.; Abdullah, L. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2019)
This study aimed to find out the compoSItion and distribution of thin-tailed sheep’s carcas tissue fed with green concentrate feed on the different breeding system. A total of 20 female thin-tailed sheep around 1 year old with an average initial weight of 18.3 ± 2.01, intenSIvely and semi-intenSIvely nurture for 119 days. Feed was given in the form of brachiaria humidicola grass and green concentrate with commercial concentrate as a control. Green concentrates and commercial concentrates are given in the morning at 07.00 and grass is given at 11.00, with a ratio of 40:60%. Concentrates were given with different nurture systems was carried out with four treatments, namely five sheep grazed for 6 hours with commercial concentrate feed (SIKK), five sheep grazed for 6 hours with green concentrate feed (SIIZ), five sheep grounded with grass feed and commercial concentrates (IKK), and five sheep are grounded with grass feed and green concentrate (IIZ). The experiment was carried out in a completely randomized factorial pattern with 2×2 treatments and 5 replications with initial weights as a correction factor. The results showed that sheep that were given green concentrates had lower weight, carcass weight, lower fat weight compared to commercial concentrates. However, with semi-intenSIve nurture it produces weight and percentage of muscle that is not much different from sheep that are given commercial concentrates.